Research on Improving The 9R Performance and Key Drivers of Circular Economy in The Bicycle Industry - Lai, Po-Yen; Chang, An-Yuan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The Circular Economy (CE) is recognized by scholars as a crucial tool for advancing Sustainable Development (SD). There is an urgent need to promote CE and develop an integrated model for its evaluation. Research indicates that industries face numerous challenges in implementing CE. To successfully transition to CE, it is essential to understand the key R-principle indicators and the supporting factors that facilitate this transition. This study focuses on Taiwan's bicycle industry, selected for its comprehensive supply chain system. A successful transformation in this sector could significantly benefit the overall development of Taiwan's industries. This study employs the Quality Function Deployment and the House of Quality as the fundamental framework to propose a practical model architecture, exploring how to accelerate the achievement of CE goals through driver factors. Using Fuzzy Multiple Attribute Decision Making methods, this research identifies the key driver factors for CE. The study identifies Reduce, Refuse, and Rethink as significant R principles and indicates that external funding, strong government support, enhanced industry competitiveness, government-led mandatory or voluntary social responsibility initiatives, and cost reduction are critical driver factors for realizing CE.